SOCIAL PRENEUR DALAM PENANGGULANGAN KEMISKINAN DI KECAMATAN BISSAPPU KABUPATEN BANTAENG - Agustang, Andi; Suardi, Suardi; Mutiara, Indah Ainun; Ramlan, Herdianty (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Community Service aims at striving to overcome poverty in rural communities through empowering PKK mothers by developing social principles based on social activities. Partners will be given skills in making peanut-based cakes as traditional cakes, product design skills, product packaging branding skills, and social media utilization skills as product marketing tools. The method of implementing community service activities carried out through training given to PKK RW 1 and RW 02 mothers through several stages, namely the activity planning stage, the activity implementation stage, and the evaluation phase or the end of the activity. The outputs produced in this activity are: (1) the development of bean-based cake product skills as a traditional pastry product, (2) the talent in designing product packaging, (3) the product-packaging branding skill, (4) the social media utilization skills are developed product marketing facilities.